2020
DOI: 10.48550/arxiv.2003.02679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Ehrhart Polynomial of Minimal Matroids

Luis Ferroni

Abstract: We provide a formula for the Ehrhart polynomial of the connected matroid of size n and rank k with the least number of bases, also known as a minimal matroid [10]. We prove that their polytopes are Ehrhart positive and h * -real-rooted (and hence unimodal). We use our formula for these Ehrhart polynomials to prove that the operation of circuit-hyperplane relaxation of a matroid preserves Ehrhart positivity. We state two conjectures: that indeed all matroids are h * -real-rooted, and that the coefficients of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…This result proves a conjecture posed in [7] by the first author for the case of matroids of rank 2. The key to prove Theorem 1.2 is the superadditivity of the polynomials P a i ,n (t) that is provided by Proposition 4.1.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…This result proves a conjecture posed in [7] by the first author for the case of matroids of rank 2. The key to prove Theorem 1.2 is the superadditivity of the polynomials P a i ,n (t) that is provided by Proposition 4.1.…”
Section: Introductionsupporting
confidence: 81%
“…We observe that Q 2,n agrees with the matroid polytope of the minimal matroid T 2,n . From Proposition 3.2 we therefore obtain an alternative proof for the Ehrhart polynomial of the minimal matroid T 2,n given in [7,Theorem 3…”
Section: Ehrhart Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This proves (22). Since h Fr (σ n , x) = p Fr,n,0 (x) = p r,0 n,0 (x), from the recurrence of Proposition 5.6 we get…”
Section: The R-colored Barycentric Subdivision Operator Consider the ...supporting
confidence: 51%
“…is a well studied polynomial of degree at most n with nonnegative coefficients, called the h * -polynomial of P. Stapledon [43] showed that h * (P, x) has a nonnegative symmetric decomposition with respect to n whenever P contains a lattice point in its relative interior (and in fact, to the best of our knowledge, the concept of a symmetric decomposition first appeared in [43]). While the question of unimodality of the h * -polynomial has long been studied [18], its γ-positivity and real-rootedness have been investigated more recently for several special classes of lattice polytopes [12,22,28,29,35,36,38] and the unimodality and real-rootedness of its symmetric decomposition have been addressed too [17,30,37].…”
Section: Introductionmentioning
confidence: 99%